Horizon scan of online plant trade reveals emerging invasive species and high-risk platforms - Jacob Maher; Oliver C. Stringham; John Virtue; Phillip Cassey (Biological Invasions, 2026)
Horticultural trade is the primary pathway for the introduction of invasive plant species. Increasingly, trade is conducted online via e-commerce platforms. We used automated web scraping to capture snapshots of the online plant trade in Australia across 11 e-commerce websites between 2020 and 2023, aiming to identify potentially invasive species for sale. We identified 3,822 species for sale, which we categorised based on their Australian regulatory, naturalisation and native status, as well as their evidence of impacts elsewhere. We found the sale of 194 ‘Priority’ species, which are already considered invasive in Australia; 544 ‘Attention’ species, which have naturalised in Australia; and 175 ‘Watch’ species that are invasive elsewhere in the world but have not yet naturalised in Australia. We further prioritised the 175 Watch species, highlighting four species ( Berberis thunbergii , Artemisia vulgaris , Rosa rugosa, and Elaeagnus angustifolia ) for immediate investigation based on global occupancy and abundance, climate suitability, propagule pressure, and evidence of impacts. We also evaluate invasion risk across e‑commerce platform types, finding that public online marketplaces list more plant taxa over time than nursery websites and that marketplaces and generalist nurseries tend to offer species with higher invasion risk than specialist nurseries. We recommend that this dataset is used as an aid for prioritising weed risk assessments by government authorities to prevent the establishment of new invasive plant species.

Scale of unregulated international trade in Australian reptiles and amphibians - Sebastian Chekunov; Oliver Stringham; Adam Toomes; Thomas Prowse; Phillip Cassey (Conservation Biology, 2024)
Reptiles and amphibians are popular in the exotic pet trade, where Australian species are valued for their rarity and uniqueness. Despite a near‐complete ban on the export of Australian wildlife, smuggling and subsequent international trade frequently occur in an unregulated and unmonitored manner. In 2022, Australia listed over 100 squamates in Appendix III of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) to better monitor this trade. We investigated current trade and assessed the value of this Australian CITES listing using web‐scraping methods to monitor the online pet trade in Australian reptiles and amphibians, with additional data from published papers, trade databases, and seizure records. Despite the export ban, we identified 170 endemic herpetofauna (reptile and amphibian) species in international trade, 33 of which were not recorded previously in the international market, including 6 newly recorded genera. Ninety‐two traded species were included in CITES appendices (59 added in 2022), but at least 78 other traded species remained unregulated. Among these, 5 of the 10 traded threatened species were unlisted, and we recommend they be considered for inclusion in CITES Appendix III. We also recommend the listing of all Diplodactylidae genera in Appendix III. Despite this family representing the greatest number of Australian species in trade, only one genus (of 7 traded) was included in the recent CITES amendments. Overall, a large number of Australian reptile and amphibian species are traded internationally and, although we acknowledge the value of Australia's recent CITES listing, we recommend the consideration of other taxa for similar inclusion in CITES.

Who’s a pretty bird? Predicting the traded abundance of bird species in Australian online pet trade - Katherine G. W. Hill; Oliver C. Stringham; Stephanie Moncayo; Adam Toomes; Jonathan J. Tyler; Phillip Cassey; Steven Delean (Biological Invasions, 2024)

A snapshot of online wildlife trade: Australian e-commerce trade of native and non-native pets - Adam Toomes; Stephanie Moncayo; Oliver C. Stringham; Charlotte Lassaline; Lisa Wood; Mariah Millington; Charlotte Drake; Charlotte Jense; Ashley Allen; Katherine G.W. Hill; Pablo García-Díaz; Lewis Mitchell; et al. (Biological Conservation, 2023)

The U.S. market for imported wildlife not listed in the CITES multilateral treaty - Freyja Watters; Oliver Stringham; Chris R. Shepherd; Phillip Cassey (Conservation Biology, 2022)
The international wildlife trade presents severe conservation and environmental security risks, yet no international regulatory framework exists to monitor the trade of species not listed in the appendices of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). We explored the composition and dynamics of internationally regulated versus nonregulated trade, with a focus on importations of wild‐caught terrestrial vertebrates entering the United States from 2009 to 2018. We used 10 years of species‐level trade records of the numbers of live, wild‐caught animals imported to the United States and data on International Union for the Conservation of Nature (IUCN) estimates of extinction risk to determine whether there were differences in the diversity, abundance, and risk to extinction among imports of CITES‐listed versus unlisted species. We found 3.6 times the number of unlisted species in U.S. imports compared with CITES‐listed species (1366 vs. 378 species). The CITES‐listed species were more likely to face reported conservation threats relative to unlisted species (71.7% vs. 27.5%). However, 376 unlisted species faced conversation threats, 297 species had unknown population trends, and 139 species were without an evaluation by the IUCN. Unlisted species appearing for the first time in records were imported 5.5 times more often relative to CITES‐listed species. Unlisted reptiles had the largest rate of entry, averaging 53 unique species appearing in imports for the first time per year. Overall trade quantities were approximately 11 times larger for imports of unlisted species relative to imports of CITES‐listed species. Countries that were top exporters of CITES‐listed species were mostly different from exporters of unlisted species. Because of the vulnerabilities of unlisted, traded species entering the United States and increasing global demand, we strongly recommend governments adapt their policies to monitor and report on the trade of all wildlife.

A guide to using the internet to monitor and quantify the wildlife trade - Oliver C. Stringham; Adam Toomes; Aurelie M. Kanishka; Lewis Mitchell; Sarah Heinrich; Joshua V. Ross; Phillip Cassey (Conservation Biology, 2021)
The unrivaled growth in e‐commerce of animals and plants presents an unprecedented opportunity to monitor wildlife trade to inform conservation, biosecurity, and law enforcement. Using the internet to quantify the scale of the wildlife trade (volume and frequency) is a relatively recent and rapidly developing approach that lacks an accessible framework for locating relevant websites and collecting data. We produced an accessible guide for internet‐based wildlife trade surveillance. We detailed a repeatable method involving a systematic internet search, with search engines, to locate relevant websites and content. For data collection, we highlight web‐scraping technology as an efficient way to collect data in an automated fashion at regularly timed intervals. Our guide is applicable to the multitude of trade‐based contexts because researchers can tailor search keywords for specific taxa or derived products and locations of interest. We provide information for working with the diversity of websites used in wildlife trade. For example, to locate relevant content on social media (e.g., posts or groups), each social media platform should be examined individually via the site's internal search engine. A key advantage of using the internet to study wildlife trade is the relative ease of access to an increasing amount of trade‐related data. However, not all wildlife trade occurs online and it may occur on unobservable sections of the internet.